Amorphous MoO3-x nanosheet coated carbon cloth embedded with CoNi alloy particles, preparation method of amorphous MoO3-x nanosheet coated carbon cloth and lithium-sulfur battery
By using amorphous MoO3-x nanosheets with embedded CoNi alloy particles in lithium-sulfur batteries to coat the carbon cloth as the intermediate functional layer, the problem of poor electrocatalytic conversion of polysulfides is solved, and the cycle stability and power performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202411941422.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-25
AI Technical Summary
In existing lithium-sulfur batteries, electrocatalysts are difficult to effectively catalyze the conversion of polysulfides, resulting in severe ‘shuttle effect’, low sulfur utilization rate, inactivation of lithium metal, and limited electrochemical activity.
The carbon cloth is coated with amorphous MoO3-x nanosheets with embedded CoNi alloy particles as the intermediate functional layer. The material is prepared by hydrothermal reaction and thermal reduction and annealing steps. It uses its high conductivity, strong adsorption ability and excellent catalytic performance to improve the polysulfide shuttle effect inside the battery.
It effectively alleviates the "shuttle effect" of polysulfides inside the battery, improves the battery's charge and discharge specific capacity and Coulomb efficiency, reduces the capacity attenuation rate, and improves the sulfur utilization rate and battery cycle life.
Smart Images

Figure CN119695151A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of development of functional layer materials for lithium-sulfur batteries and relates to an amorphous MoO2 with embedded CoNi alloy particles. 3-x Nanosheet-coated carbon cloth, preparation method thereof and a lithium-sulfur battery. Background Art
[0002] In the electrochemical energy storage system, lithium-sulfur batteries that use lithium metal as the negative electrode and sulfur as the positive electrode have an extremely high theoretical specific capacity of 1675mAh / g and an energy density of 2600 Wh / kg, which is more than five times the energy density of current commercial lithium-ion batteries and can meet the longer endurance requirements of many technical industries. In addition, lithium-sulfur batteries are low-cost and environmentally compatible, and are expected to replace lithium-ion batteries as a high-energy chemical power system. However, the industrialization process of lithium-sulfur batteries is difficult to break through in reality. For example, the "shuttle effect" of soluble polysulfides in the electrolyte leads to the loss of active substances, which in turn affects the cycle stability and efficiency of the battery. At the same time, the slow reaction kinetics, volume expansion, and dendrite growth on the surface of metallic lithium during the charge and discharge process will cause damage to the internal structure of the battery and reduce the service life of the battery. Moreover, the poor electronic conductivity of pure sulfur also limits the power performance of the battery.
[0003] In response to the above problems, a large number of research works have explored improving the performance of lithium-sulfur batteries from different parts of the battery structure, including the construction of sulfur positive electrode materials, membrane modification, functional layer materials, regulation of the electrolyte system, and protection of the lithium negative electrode. Applying a functional layer in the internal structure of a lithium-sulfur battery is an effective way to capture and limit the shuttling of polysulfides. The role of the functional layer is to implement effective catalytic conversion of polysulfides while providing additional physical and chemical barriers to reduce the "shuttle effect" of polysulfides and improve the battery's cycle stability and rate performance. However, the existing intermediate functional layer still needs to be improved in improving the "shuttle effect" of polysulfides, and the electrochemical activity of the battery is still limited. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides an amorphous MoO2 embedded with CoNi alloy particles. 3-x Nanosheet-coated carbon cloth, preparation method thereof and a lithium-sulfur battery are provided to solve the technical problems in the prior art that electrocatalysts are difficult to effectively catalyze and convert polysulfides, resulting in severe "shuttle effect", low sulfur utilization, lithium metal deactivation and limited electrochemical activity.
[0005] The present invention is achieved through the following technical solutions: Amorphous MoO with embedded CoNi alloy particles 3-x The method for preparing nanosheet-coated carbon cloth comprises the following steps: S1: Add cobalt chloride, nickel chloride, ammonium molybdate and urea into water, stir and dissolve them to form solution A; S2: Add the acidified carbon fiber cloth to the solution A, perform a hydrothermal reaction, and then dry to obtain the precursor Co 0.5 Ni 0.5 MoO4 coated carbon cloth; S3: In a mixed gas atmosphere of hydrogen and argon, the precursor Co 0.5 Ni 0.5 The MoO4 coated carbon cloth is subjected to thermal reduction annealing to obtain the amorphous MoO4 embedded with CoNi alloy particles. 3-x Nanosheets coated with carbon cloth.
[0006] Preferably, in step S1, the mass ratio of cobalt chloride to nickel chloride, ammonium molybdate and urea is (2-6):(2-6):(3-9):(1-3).
[0007] Preferably, in step S2, the temperature of the hydrothermal reaction is 100-140° C., and the time of the hydrothermal reaction is 8-16 hours.
[0008] Preferably, in step S2, the drying temperature is 60-100° C., and the drying time is 6-12 h.
[0009] Preferably, in step S2, the acidified carbon fiber cloth is prepared by immersing the carbon fiber cloth in nitric acid, followed by washing and drying.
[0010] Preferably, in step S3, in the mixed gas atmosphere of hydrogen and argon, the volume ratio of hydrogen to argon is (5-10):(90-95).
[0011] Preferably, in step S3, during the thermal reduction annealing process, the reduction temperature is 450-600° C., and the reduction time is 2.5-4 h.
[0012] Amorphous MoO with embedded CoNi alloy particles 3-x The nanosheet-coated carbon cloth is prepared by the above method.
[0013] An intermediate functional layer of a lithium-sulfur battery, comprising an amorphous MoO2 embedded with CoNi alloy particles 3-x Made of nanosheets coated with carbon cloth.
[0014] 10. A lithium-sulfur battery, characterized in that it comprises the intermediate functional layer of a lithium-sulfur battery according to claim 9; the lithium-sulfur battery has a reversible specific capacity of 600-700 mAh / g after 500 cycles at a rate of 1C in the voltage range of 1.7-2.8 V.
[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention discloses an amorphous MoO2 embedded with CoNi alloy particles. 3-x The method for preparing nanosheet-coated carbon cloth comprises the following steps: firstly, the method adopts the acidified carbon fiber cloth as the substrate, the carbon fiber cloth has good flexibility and conductivity, and can accelerate the transfer of electrons; in addition, the acidified carbon fiber cloth can enhance the active sites on the surface of the carbon fiber cloth, which is beneficial to the subsequent deposition process; and the acidification treatment further enhances the bonding force between the substrate and the deposition layer, and improves the overall stability of the material; secondly, the amorphous MoO2 with embedded CoNi alloy particles is deposited on the acidified carbon fiber cloth. 3-x Nanosheets, CoNi alloy particles have excellent high conductivity, while amorphous MoO 3-x Nanosheets have a large specific surface area, strong adsorption capacity and excellent catalytic performance. When used as the middle layer of lithium-sulfur batteries, they can achieve good chemical adsorption and catalytic conversion of polysulfides inside the battery, effectively alleviating the "shuttle effect" of polysulfides inside the battery, improving the battery's charge and discharge specific capacity and coulombic efficiency, reducing the capacity attenuation rate, and improving the utilization rate of sulfur and the battery cycle life.
[0016] Furthermore, in step S1, the mass ratio of cobalt chloride to nickel chloride, ammonium molybdate and urea is (2-6):(2-6):(3-9):(1-3). First, cobalt chloride and nickel chloride are used as the main metal salt sources, and their appropriate ratio helps to form uniform CoNi alloy particles. Within this mass ratio range, the two can fully react to form a stable alloy structure, thereby improving the reactivity of the material; ammonium molybdate, as a molybdenum source, not only participates in the amorphous MoO 3-x The formation of nanosheets also plays a catalytic role to a certain extent. The appropriate amount of ammonium molybdate can accelerate the reaction process and promote the formation of amorphous MoO 3-x The growth of nanosheets and the embedding of CoNi alloy particles; urea is a regulator, and its appropriate addition can control the pH value and ionic strength of the solution, thereby affecting the morphology and structure of the material. Within this mass ratio range, urea can optimize the reaction conditions and promote the uniform growth and dispersion of the material.
[0017] Furthermore, in step S2, the temperature of the hydrothermal reaction is 100-140 °C, and the time of the hydrothermal reaction is 8-16 hours. Within this temperature range, the reactant molecules can obtain sufficient energy to overcome the reaction barrier and promote the full progress of the chemical reaction, which helps to form a precursor Co with stable structure and uniform composition. 0.5 Ni 0.5 MoO4 coated carbon cloth; In addition, the appropriate hydrothermal reaction temperature and time can control the growth rate and morphology of the material. Under this condition, Co0.5 Ni 0.5 MoO4 nanosheets can be evenly deposited on carbon fiber cloth; in addition, long-term high-temperature reaction helps the crystallization and purification of the material, thereby enhancing the stability and electrochemical properties of the material; at the same time, during the hydrothermal reaction, chemical bonding will occur between the reactant molecules to form a stable chemical bond connection. This chemical bond connection can enhance the binding force of the components within the material and improve the overall stability and durability of the material.
[0018] Furthermore, in step S2, the drying temperature is 60-100°C and the drying time is 6-12 h. Within this temperature and time range, the moisture in the material can be effectively evaporated and removed. Appropriate drying temperature and time can ensure that the moisture escapes from the material at a faster rate, while avoiding excessively high temperatures that cause damage to the material structure or decomposition of components, thereby maintaining the structural stability and integrity of the material, which is crucial for the subsequent thermal reduction annealing step and the performance of the final material. In addition, appropriate drying temperature and time can avoid the generation of internal stress in the material during the rapid drying process, causing the material to crack or deform, which is beneficial for maintaining the flatness and uniformity of the material and improving the overall performance of the material.
[0019] Further, in step S2, the preparation of the acidified carbon fiber cloth is as follows: the carbon fiber is arranged in nitric acid for immersion treatment, and then washed and dried. The nitric acid immersion treatment can also introduce a large number of oxygen-containing functional groups (such as carboxyl, hydroxyl, etc.) on the surface of the carbon fiber cloth. These functional groups can enhance the reactive sites of the carbon fiber cloth, which is conducive to the subsequent chemical reaction, and also helps to improve the electrochemical properties of the material; in addition, the strong oxidizing property of nitric acid can remove impurities such as oil and dust on the surface of the carbon fiber cloth, thereby improving the purity and quality of the material, which is beneficial for the interface bonding and performance improvement during the subsequent preparation of composite materials; in addition, the nitric acid immersion treatment will also have a certain effect on the internal structure of the carbon fiber cloth, optimize the arrangement of the fibers, reduce internal defects, etc., and these optimizations help to further improve the mechanical properties and stability of the material. The acidified carbon fiber cloth provides a good substrate for the subsequent hydrothermal reaction and deposition process, which helps to enhance the bonding force between the deposition layer and the substrate, thereby preparing a composite material with stable structure and excellent performance.
[0020] Further, in step S3, in the mixed gas atmosphere of hydrogen and argon, the volume ratio of hydrogen to argon is (5~10): (90~95). By adjusting the volume ratio of hydrogen to argon, the rate of the reduction reaction can be flexibly controlled. Within this ratio range, hydrogen can provide sufficient reducing ability while avoiding the destruction of the material structure or morphological changes caused by too fast a reaction rate. Therefore, this mixed gas ratio helps to maintain the sheet morphology of the material; hydrogen, as a reducing gas, can participate in the reduction reaction and reduce the metal ions in the precursor to metal particles. Within this volume ratio range, hydrogen can provide sufficient reducing atmosphere to promote the precipitation and growth of alloy particles. The appropriate volume ratio of hydrogen to argon helps to optimize the precipitation conditions of alloy particles. Hydrogen can penetrate into the material to promote the reduction of metal ions and the formation of alloy particles, while argon plays a protective role to prevent the material from undergoing unnecessary chemical reactions at high temperatures. This optimized precipitation condition helps to obtain alloy particles with uniform distribution and appropriate size. In addition, during the reduction process, hydrogen also has the effect of preventing particle agglomeration. Since hydrogen can provide a reducing atmosphere and promote the precipitation of particles, it can reduce the interaction between particles and prevent them from agglomerating. This helps to obtain alloy particles with good dispersion and uniform single particle size. At the same time, CoNi alloy particles can also be effectively embedded in nanosheets to form a composite material with excellent performance.
[0021] Furthermore, in step S3, during the thermal reduction annealing process, the reduction temperature is 450~600 ℃, and the reduction time is 2.5~4 h. First, the material can maintain its flaky morphology by reducing it at 450~600 ℃ for 2.5~4 h, and the metal ions can obtain enough energy for the reduction reaction by treating it at the reduction temperature of 450~600 ℃ for 2.5~4 h, thereby forming alloy particles. As the temperature increases, the reduction reaction rate accelerates, and the precipitation rate of the alloy particles also increases accordingly. However, too high a temperature will cause the particles to agglomerate or be too large in size, while the appropriate temperature can ensure the uniform precipitation of the alloy particles. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0023] Figure 1 The present invention is an amorphous MoO embedded with CoNi alloy particles. 3-x Schematic diagram of the preparation process of nanosheet-coated carbon cloth; Figure 2 The present invention is an amorphous MoO embedded with CoNi alloy particles 3-x Macroscopic photo of nanosheet-coated carbon cloth; Figure 3 The amorphous MoO2 with embedded CoNi alloy particles prepared in Example 1 of the present invention 3-x SEM images of the surface of nanosheet-coated carbon cloth at different magnifications, where the scale in (a) is 500nm and (b) is 200nm; Figure 4 The amorphous MoO2 with embedded CoNi alloy particles prepared in Example 1 of the present invention 3-x TEM images of the surface of nanosheet-coated carbon cloth at different magnifications, where the scale bar in the figure (a) is 50 nm and (b) is 20 nm; Figure 5 The amorphous MoO2 with embedded CoNi alloy particles prepared in Example 1 of the present invention 3-x Element mapping distribution diagram of nanosheet-coated carbon cloth; Figure 6 The amorphous MoO2 with embedded CoNi alloy particles prepared in Example 1 of the present invention 3-x XRD pattern of powder on the surface of nanosheet-coated carbon cloth; Figure 7 The amorphous MoO2 with embedded CoNi alloy particles prepared by Example 1 of the present invention is 3-x The charge and discharge curves of a lithium-sulfur battery assembled with nanosheet-coated carbon cloth as the intermediate functional layer. DETAILED DESCRIPTION
[0024] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0025] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0026] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0027] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0028] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0029] like Figure 1 As shown, the present invention provides an amorphous MoO embedded with CoNi alloy particles. 3-x The method for preparing nanosheet-coated carbon cloth comprises the following steps: S1: Add cobalt chloride, nickel chloride, ammonium molybdate and urea into water, stir and dissolve them to form solution A; specifically, stir cobalt chloride (CoCl2·6H2O), nickel chloride (NiCl2·6H2O), ammonium molybdate ((NH4)2MoO4·2H2O) and urea (CO(NH2)2) in deionized water to form a purple-red solution; Among them, the mass ratio of cobalt chloride to nickel chloride to ammonium molybdate to urea is (2~6):(2~6):(3~9):(1~3).
[0030] S2: Add the acidified carbon cloth (CC) to the above solution A, transfer it to a high-pressure reactor for hydrothermal growth, and dry it to obtain the precursor Co 0.5 Ni 0.5 MoO4 coated carbon cloth; The hydrothermal growth temperature is 100-140 °C, the time is 8-16 h, and the drying temperature is 60-100 °C, the time is 6-12 h. The acidified carbon fiber cloth is prepared by immersing the carbon fiber in nitric acid, washing and drying the carbon fiber cloth. The preferred mass concentration of the nitric acid is 69%, and the immersion time is 6 hours. S3: Co in a mixed gas atmosphere of hydrogen and argon (H2 / Ar) 0.5 Ni 0.5 MoO4 coated carbon cloth was subjected to thermal reduction annealing to obtain amorphous MoO4 embedded with CoNi alloy particles. 3-x Nanosheets coated with carbon cloth (CoNi / MoO 3-x @CC).
[0031] Among them, the volume ratio of H2 and Ar is (5~10):(90~95), and during the thermal reduction process, the reduction temperature is 450~600℃, and the reduction time is 2.5~4 h.
[0032] In addition, the present invention also discloses an intermediate functional layer of a lithium-sulfur battery, which is formed by embedding CoNi alloy particles in an amorphous MoO 3-x Specifically, the obtained amorphous MoO2 with embedded CoNi alloy particles is prepared by coating carbon cloth with nanosheets. 3-x The nanosheet-coated carbon cloth is cut into suitable sizes by a cutting machine to serve as the intermediate functional layer of the lithium-sulfur battery. Preferably, the nanosheet-coated carbon cloth is cut into 12-16 mm round pieces.
[0033] At the same time, the present invention also discloses a lithium-sulfur battery, which comprises an intermediate functional layer, a positive electrode, a negative electrode, an electrolyte and a separator of a lithium-sulfur battery prepared by the present invention. The lithium-sulfur battery has a reversible specific capacity of 600-700 mAh / g after 500 cycles at a voltage range of 1.7-2.8 V and a rate of 1C.
[0034] The present invention discloses an amorphous MoO2 embedded with CoNi alloy particles. 3-x The preparation method of nanosheet-coated carbon cloth comprises the following steps: fully stirring cobalt chloride, nickel chloride, ammonium molybdate and urea in deionized water to form a purple-red solution; adding the acidified carbon cloth CC to the above solution, and transferring the carbon cloth CC to a high-pressure reactor for hydrothermal growth to obtain a precursor Co 0.5 Ni 0.5 MoO4 coated carbon cloth; Co 0.5 Ni 0.5 MoO4 coated carbon cloth was subjected to thermal reduction annealing, and the Co 0.5 Ni 0.5 The MoO4 nanosheet precursor was reduced to CoNi alloy particles and MoO 3-x Amorphous nanosheets, CoNi / MoO 3-x @CC. The present invention uses carbon cloth as a substrate, Co 0.5 Ni 0.5 MoO4 nanosheets are staggered and grown on carbon fibers. After high-temperature thermal reduction, CoNi alloy particles are embedded in amorphous MoO 3-x In the nanosheets, the original nanosheet morphology is maintained, and the carbon cloth substrate ensures that the material has good mechanical strength and guarantees the high specific surface area of the nanosheet structure.
[0035] Amorphous MoO2 embedded with CoNi alloy particles prepared by the present invention 3-x Macroscopic photos of the nanosheet functional layer are shown in Figure 2The carbon cloth in this material is conductive, and it also has high conductivity of alloy particles and amorphous MoO 3-x The strong adsorption capacity and excellent catalytic performance of the lithium-sulfur battery can effectively improve the shuttle effect of polysulfide, improve the utilization rate of sulfur, increase the charge and discharge capacity of the battery, reduce the capacity decay rate during the reaction, and have excellent electrochemical performance. The preparation method requires simple equipment, the process is safe and harmless, and the preparation cycle is short. The prepared product has good electrical conductivity, chemical adsorption and catalytic activity, and is suitable for large-scale production.
[0036] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0037] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0038] Example 1 Amorphous MoO with embedded CoNi alloy particles 3-x The method for preparing a nanosheet-coated carbon cloth functional layer comprises the following steps: Cobalt chloride (0.24 g), nickel chloride (0.24 g), ammonium molybdate (0.36 g) and urea (0.12 g) were stirred in 20 mL of deionized water for 0.5 h to form a purple-red solution. 2×2 cm carbon cloth (CC) acidified with concentrated nitric acid was added to the mixed solution and transferred to a 30 mL polytetrafluoroethylene-lined stainless steel autoclave. The sealed stainless steel autoclave was heated to 120 °C and maintained for 12 h to obtain the precursor Co 0.5 Ni 0.5 MoO4 coated carbon cloth was dried in an oven at 60 °C for 12 h. Co 0.5 Ni 0.5 MoO4 coated carbon cloth was thermally reduced for 3.5 h at a reduction temperature of 500 °C and a heating rate of 5 °C / min. After natural cooling in the tube furnace, amorphous MoO4 with embedded CoNi alloy particles was obtained. 3-xNanosheets coated with carbon cloth intermediate layer CoNi / MoO 3-x @CC.
[0039] The amorphous MoO embedded with CoNi alloy particles prepared in this embodiment 3-x SEM images of the nanosheet functional layer Figure 3 , TEM Figure 4 .Depend on Figure 3 It can be seen that the amorphous MoO2 with embedded CoNi alloy particles prepared by the present invention 3-x The surface of the nanosheet functional layer is composed of interlaced nanosheets, and particles are precipitated on the nanosheets. Figure 4 It can be seen that Co 2+ and Ni 2+ It will be reduced to CoNi alloy particles with a diameter of 20 nm and evenly distributed in the amorphous MoO 3-x On nanosheets.
[0040] The amorphous MoO embedded with CoNi alloy particles prepared in this embodiment 3-x The results of the mapping test of the nanosheet functional layer are shown in Figure 5 ,Depend on Figure 5 It can be seen that Mo and O are evenly distributed on the nanosheets, while Co and Ni are mainly concentrated in the nanoparticles, forming an amorphous MoO with embedded CoNi alloy particles. 3-x Nanosheet functional layer.
[0041] At the same time, the amorphous MoO embedded with CoNi alloy particles prepared in this embodiment 3-x The surface powder of the carbon cloth in the nanosheet functional layer was scraped off and the powder was subjected to XRD test. The characterization results are shown in Figure 6 ,Depend on Figure 6 It can be seen that there are 3 obvious peaks in the product, corresponding to the diffraction peaks of CoNi alloy (PDF#01-074-5694), and no other impurity peaks, indicating that Co 2+ and Ni 2+ is well reduced to alloy particles, while MoO 3-x It is an amorphous phase.
[0042] In order to further verify the amorphous MoO embedded with CoNi alloy particles 3-x The performance of the battery when the nanosheet functional layer is used as the intermediate functional layer of the lithium-sulfur battery. The above materials are cut into discs with a diameter of 12 mm by a cutting machine, used as the intermediate functional layer of the lithium-sulfur battery, and assembled into a lithium-sulfur battery. The charge and discharge performance of the battery is tested. The test results are shown in Figure 7 ,Depend on Figure 7 It can be seen that the lithium-sulfur battery obtained in this embodiment has a discharge capacity of 652 mAh / g after 500 cycles at a current density of 1C.
[0043] Example 2 Amorphous MoO with embedded CoNi alloy particles 3-x The method for preparing a nanosheet functional layer comprises the following steps: Cobalt chloride (0.36 g), nickel chloride (0.36 g), ammonium molybdate (0.54 g) and urea (0.18 g) were stirred in 30 mL of deionized water for 0.5 h to form a purple-red solution. 2×2 cm carbon cloth (CC) acidified with concentrated nitric acid was added to the mixed solution and transferred to a 40 mL polytetrafluoroethylene-lined stainless steel autoclave. The sealed stainless steel autoclave was heated to 140 °C and maintained for 8 h to obtain the precursor Co 0.5 Ni 0.5 MoO4 coated carbon cloth was dried in an oven at 80 °C for 10 h; Co 0.5 Ni 0.5 MoO4 coated carbon cloth was thermally reduced for 2.5 h at a reduction temperature of 600 °C and a heating rate of 5 °C / min. After natural cooling in a tube furnace, amorphous MoO4 with embedded CoNi alloy particles was obtained. 3-x Nanosheets coated with carbon cloth intermediate layer CoNi / MoO 3-x @CC.
[0044] The above material was cut into 12 mm discs by a cutting machine as the intermediate functional layer of the lithium-sulfur battery, and a lithium-sulfur battery was further prepared through the lithium-sulfur battery intermediate layer. The lithium-sulfur battery obtained in this embodiment had a discharge specific capacity of 662 mAh / g after 500 cycles at a current density of 1C.
[0045] Example 3 Amorphous MoO with embedded CoNi alloy particles 3-x The method for preparing a nanosheet functional layer comprises the following steps: Cobalt chloride (0.48 g), nickel chloride (0.48 g), ammonium molybdate (0.72 g) and urea (0.24 g) were stirred in 40 mL of deionized water for 0.5 h to form a purple-red solution. A 4×4 cm carbon cloth (CC) acidified with concentrated nitric acid was added to the mixed solution and transferred to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave. The sealed stainless steel autoclave was heated to 130 °C and maintained for 10 h to obtain the precursor Co 0.5 Ni 0.5 MoO4 coated carbon cloth was dried in an oven at 80 °C for 10 h. Co 0.5 Ni 0.5MoO4 coated carbon cloth was thermally reduced for 3 h at a reduction temperature of 550 °C and a heating rate of 5 °C / min. After natural cooling in the tube furnace, amorphous MoO4 with embedded CoNi alloy particles was obtained. 3-x Nanosheets coated with carbon cloth intermediate layer CoNi / MoO 3-x @CC.
[0046] The above material was cut into 14 mm discs by a cutting machine as the intermediate functional layer of the lithium-sulfur battery, and a lithium-sulfur battery was further prepared through the lithium-sulfur battery intermediate layer. The lithium-sulfur battery obtained in this embodiment had a discharge specific capacity of 693 mAh / g after 500 cycles at a current density of 1C.
[0047] Example 4 Amorphous MoO with embedded CoNi alloy particles 3-x The method for preparing a nanosheet functional layer comprises the following steps: Cobalt chloride (0.48 g), nickel chloride (0.48 g), ammonium molybdate (0.72 g) and urea (0.36 g) were stirred in 40 mL of deionized water for 0.5 h to form a purple-red solution. A 4×4 cm carbon cloth (CC) acidified with concentrated nitric acid was added to the mixed solution and transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave. The sealed stainless steel autoclave was heated to 140 °C and maintained for 10 h to obtain the precursor Co 0.5 Ni 0.5 MoO4 coated carbon cloth was dried in an oven at 60 °C for 10 h. Co 0.5 Ni 0.5 MoO4 coated carbon cloth was thermally reduced for 4 h at a reduction temperature of 450 °C and a heating rate of 5 °C / min. After natural cooling in the tube furnace, amorphous MoO4 with embedded CoNi alloy particles was obtained. 3-x Nanosheets coated with carbon cloth intermediate layer CoNi / MoO 3-x @CC.
[0048] The above material was cut into 14 mm discs by a cutting machine as the intermediate functional layer of the lithium-sulfur battery, and a lithium-sulfur battery was further prepared through the lithium-sulfur battery intermediate layer. The lithium-sulfur battery obtained in this embodiment had a discharge specific capacity of 624 mAh / g after 500 cycles at a current density of 1 C.
[0049] Example 5 Amorphous MoO with embedded CoNi alloy particles 3-x The method for preparing a nanosheet functional layer comprises the following steps: Cobalt chloride (0.60 g), nickel chloride (0.60 g), ammonium molybdate (0.9 g) and urea (0.4 g) were stirred in 60 mL of deionized water for 0.5 h to form a purple-red solution. A 4×4 cm carbon cloth (CC) acidified with concentrated nitric acid was added to the mixed solution and transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave. The sealed stainless steel autoclave was heated to 120 °C and maintained for 12 h to obtain the precursor Co 0.5 Ni 0.5 MoO4 coated carbon cloth was dried in an oven at 60 °C for 12 h. Co 0.5 Ni 0.5 MoO4 coated carbon cloth was thermally reduced for 3.5 h at a reduction temperature of 500 °C and a heating rate of 5 °C / min. After natural cooling in the tube furnace, amorphous MoO4 with embedded CoNi alloy particles was obtained. 3-x Nanosheets coated with carbon cloth intermediate layer CoNi / MoO 3-x @CC.
[0050] The above material was cut into 16 mm discs by a cutting machine as the intermediate functional layer of the lithium-sulfur battery, and a lithium-sulfur battery was further prepared through the lithium-sulfur battery intermediate layer. The lithium-sulfur battery obtained in this embodiment had a discharge specific capacity of 662 mAh / g after 500 cycles at a current density of 1C.
[0051] Example 6 Amorphous MoO with embedded CoNi alloy particles 3-x The method for preparing a nanosheet functional layer comprises the following steps: Cobalt chloride (0.24 g), nickel chloride (0.24 g), ammonium molybdate (0.36 g) and urea (0.36 g) were stirred in 20 mL of deionized water for 0.5 h to form a purple-red solution. 2×2 cm carbon cloth (CC) acidified with concentrated nitric acid was added to the mixed solution and transferred to a 40 mL polytetrafluoroethylene-lined stainless steel autoclave. The sealed stainless steel autoclave was heated to 130 °C and maintained for 10 h to obtain the precursor Co 0.5 Ni 0.5 MoO4 coated carbon cloth was dried in an oven at 60 °C for 10 h. Co 0.5 Ni 0.5 MoO4 coated carbon cloth was thermally reduced for 3.5 h at a reduction temperature of 500 °C and a heating rate of 5 °C / min. After natural cooling in the tubular furnace, amorphous MoO4 with embedded CoNi alloy particles was obtained. 3-x Nanosheets coated with carbon cloth intermediate layer CoNi / MoO3-x @CC.
[0052] The above material was cut into 14 mm discs by a cutting machine as the intermediate functional layer of the lithium-sulfur battery, and a lithium-sulfur battery was further prepared through the lithium-sulfur battery intermediate layer. The lithium-sulfur battery obtained in this embodiment had a discharge specific capacity of 642 mAh / g after 500 cycles at a current density of 1C.
[0053] Example 7 Amorphous MoO with embedded CoNi alloy particles 3-x The method for preparing a nanosheet functional layer comprises the following steps: Cobalt chloride (0.5 g), nickel chloride (0.5 g), ammonium molybdate (0.75 g) and urea (0.5 g) were stirred in 40 mL of deionized water for 0.5 h to form a purple-red solution. 2×2 cm carbon cloth (CC) acidified with concentrated nitric acid was added to the mixed solution and transferred to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave. The sealed stainless steel autoclave was heated to 110 °C and maintained for 14 h to obtain the precursor Co 0.5 Ni 0.5 MoO4 coated carbon cloth was dried in an oven at 80 °C for 9 h. Co 0.5 Ni 0.5 MoO4 coated carbon cloth was thermally reduced for 3 h at a reduction temperature of 550 °C and a heating rate of 5 °C / min. After natural cooling in the tube furnace, amorphous MoO4 with embedded CoNi alloy particles was obtained. 3-x Nanosheets coated with carbon cloth intermediate layer CoNi / MoO 3-x @CC.
[0054] The above material was cut into 12 mm discs by a cutting machine as the intermediate functional layer of the lithium-sulfur battery, and a lithium-sulfur battery was further prepared through the lithium-sulfur battery intermediate layer. The lithium-sulfur battery obtained in this embodiment had a discharge specific capacity of 633 mAh / g after 500 cycles at a current density of 1C.
[0055] Example 8 Amorphous MoO with embedded CoNi alloy particles 3-x The method for preparing a nanosheet functional layer comprises the following steps: Cobalt chloride (0.4 g), nickel chloride (0.4 g), ammonium molybdate (0.6 g) and urea (0.48 g) were stirred in 30 mL of deionized water for 0.5 h to form a purple-red solution. 2×2 cm carbon cloth (CC) acidified with concentrated nitric acid was added to the mixed solution and transferred to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave. The sealed stainless steel autoclave was heated to 120 °C and maintained for 12 h to obtain the precursor Co 0.5 Ni 0.5 MoO4 coated carbon cloth was dried in an oven at 60 °C for 9 h. Co 0.5 Ni 0.5 MoO4 coated carbon cloth was thermally reduced for 3.5 h at a reduction temperature of 500 °C and a heating rate of 5 °C / min. After natural cooling in the tube furnace, amorphous MoO4 with embedded CoNi alloy particles was obtained. 3-x Nanosheets coated with carbon cloth intermediate layer CoNi / MoO 3-x @CC.
[0056] The above material was cut into 14 mm discs by a cutting machine as the intermediate functional layer of the lithium-sulfur battery, and a lithium-sulfur battery was further prepared through the lithium-sulfur battery intermediate layer. The lithium-sulfur battery obtained in this embodiment had a discharge specific capacity of 646 mAh / g after 500 cycles at a current density of 1C.
[0057] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. Amorphous MoO with embedded CoNi alloy particles 3-x The method for preparing nanosheet-coated carbon cloth is characterized in that: The following steps are involved: S1: Add cobalt chloride, nickel chloride, ammonium molybdate and urea into water, stir and dissolve them to form solution A; S2: Add the acidified carbon fiber cloth to the solution A, perform a hydrothermal reaction, and then dry to obtain the precursor Co 0.5 Ni 0.5 MoO4 coated carbon cloth; S3: In a mixed gas atmosphere of hydrogen and argon, the precursor Co 0.5 Ni 0.5 The MoO4 coated carbon cloth is subjected to thermal reduction annealing to obtain the amorphous MoO4 embedded with CoNi alloy particles. 3-x Nanosheets coated with carbon cloth.
2. Amorphous MoO embedded with CoNi alloy particles according to claim 1 3-x The method for preparing nanosheet-coated carbon cloth is characterized in that: In step S1, the mass ratio of cobalt chloride to nickel chloride, ammonium molybdate and urea is (2-6):(2-6):(3-9):(1-3).
3. Amorphous MoO2 embedded with CoNi alloy particles according to claim 1 3-x The method for preparing nanosheet-coated carbon cloth is characterized in that: In step S2, the temperature of the hydrothermal reaction is 100-140° C., and the time of the hydrothermal reaction is 8-16 hours.
4. The amorphous MoO2 embedded with CoNi alloy particles according to claim 1 3-x The method for preparing nanosheet-coated carbon cloth is characterized in that: In step S2, the drying temperature is 60-100°C and the drying time is 6-12 h.
5. The amorphous MoO2 embedded with CoNi alloy particles according to claim 1 3-x The method for preparing nanosheet-coated carbon cloth is characterized in that: In step S2, the acidified carbon fiber cloth is prepared by immersing the carbon fiber cloth in nitric acid, then washing and drying the carbon fiber cloth.
6. The amorphous MoO2 embedded with CoNi alloy particles according to claim 1 3-x The method for preparing nanosheet-coated carbon cloth is characterized in that: In step S3, in the mixed gas atmosphere of hydrogen and argon, the volume ratio of hydrogen to argon is (5-10):(90-95).
7. The amorphous MoO2 embedded with CoNi alloy particles according to claim 1 3-x The method for preparing nanosheet-coated carbon cloth is characterized in that: In step S3, during the thermal reduction annealing process, the reduction temperature is 450-600°C and the reduction time is 2.5-4 h.
8. Amorphous MoO with embedded CoNi alloy particles 3-x Nanosheet-coated carbon cloth, characterized in that: Prepared by the method according to any one of claims 1 to 7.
9. An intermediate functional layer of a lithium-sulfur battery, characterized in that: The amorphous MoO embedded with CoNi alloy particles as claimed in claim 8 3-x Made of nanosheets coated with carbon cloth.
10. A lithium-sulfur battery, characterized in that: A middle functional layer comprising a lithium-sulfur battery as claimed in claim 9; the lithium-sulfur battery has a reversible specific capacity of 600-700 mAh / g after 500 cycles at a voltage range of 1.7-2.8 V and a rate of 1C.